The Impact of Live Streaming on Consumer Purchase Decisions on Instagram: A Case Study of Aurell Shop : PENGARUH LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI INSTAGRAM: STUDI KASUS PADA AURELL SHOP - Yunanda, Agung Putra; Emely, Bamy; Tamara, Selvi Yona; Risvianza , Tasya (Green Engineering Society, 2025)
In today's digital era, rapid technological advancements have significantly accelerated the growth of social media. One of the most popular platforms, especially among young people, is Instagram. The live streaming feature on social media platforms like Instagram plays a crucial role in influencing consumer purchasing decisions. Through live streaming, businesses can offer attractive promotions such as exclusive discounts available only during the live session, creating a sense of urgency for consumers to make immediate purchases. This feature also allows products to be showcased in real-time and facilitates direct interaction between sellers and potential buyers, which can ultimately increase interest in making a purchase. In addition to direct engagement, the availability of discounts also serves as a strong appeal that encourages consumers to watch and buy during the live session. Abstrak. Di era digital saat ini, kemajuan teknologi yang pesat telah memicu pertumbuhan media sosial secara drastis. Salah satu platform yang sangat populer, terutama di kalangan anak muda, adalah Instagram. Fitur siaran langsung (live streaming) pada platform media sosial seperti Instagram memungkinkan pengguna untuk menyiarkan video secara real-time kepada audiens mereka memainkan peran penting dalam mempengaruhi keputusan pembelian konsumen. Melalui live streaming, pelaku usaha dapat memberikan promosi menarik seperti diskon eksklusif yang hanya tersedia selama sesi berlangsung, sehingga menciptakan urgensi bagi konsumen untuk segera membeli. Tayangan langsung ini juga memperlihatkan produk secara real-time serta memungkinkan komunikasi langsung antara penjual dan calon pembeli, yang pada akhirnya dapat meningkatkan minat untuk membeli. Selain interaksi langsung, adanya potongan harga juga menjadi daya tarik tersendiri yang membuat konsumen lebih tertarik untuk menonton dan melakukan pembelian.